CRUSTAL TECTONIC FRAMEWORK OF NORTHERN XINJIANG AND ADJACENT REGIONS AND ITS FORMATION - Li J.; Sun G.; Yang T.; Gao L.; Zhu Z.; He G.; Xu X.; Li H. (My University, 2006)
Based on the geological data the authors collected in northern Xinjiang in the last two decades, together with a comprehensive analysis on the existent geological and geophysical data, they discussed the present-day crustal tectonic framework of northern Xinjiang and adjacent regions and its formation process. The basic present-day tectonic feature is a vertically two-layer structure and horizontally various tectonic subdivisions in different stages. Horizontally, the Cenozoic was characterized by a basin-and-range structure and the late Paleozoic was generally featured by a mosaic of Phanerozoic orogenic belts and ancient blocks, which includes two orocline orogenic systems, two en enchlon broom-like structures and three linear orogenic systems, being separately to the Siberian, Kazakhstan, Tarim and Karatag plates. The Karatag Plate is composed of an island arc with a Neoproterozoic basement and surrounding oceanic lithosphere, and its remnants are preserved in the South Tianshan collision zone and has a range from South Tianshan eastward to Beishan and central Inner Mongolia. The Altay, East Junggar, Junggar - Turpan - Hami blocks are parts of the Siberian Plate, and the western Junggar and Central Asian areas are components of the Kazakhstan Plate. The Charask-Zaysan, Eren Habirga and Kanguertag belts are taken as the southern border of the Seberian Plate and South Tianshan is taken as the collision zone between the Kazakhstan and Tarim plates. Vertically, the crust of the study area is divided into three structural layers, Sinian - Carboniferous, Permian - Jurassic and post-Cretaceous. The formation of this tectonic framework falls into three stages, Mesoproterozoic - late Paleozoic in which there were the evolution and closing of oceans, Permian - Jurassic, which saw the influence of the evolution of the Paleo-Pacific and Paleo-Tethys oceans, and the Cenozoic in which there is the influence of the India - Eurasia collision. Some times in the process there was reworking of diapir of mantle-sourced magma on the crust or lithosphere. Previous oceans in the area include the Paleo-Pacific and Paleo-Asian oceans. Dynamically, the formation and evolution of the crust were controlled horizontally by the interaction between plates and vertically by the interaction between the asthenosphere and overlying lithosphere or crust, and as a result, the accretion of the continental crust was on both the horizontal and vertical directions and the crustal evolution shows both compression and extension.
Keywords: CRUSTAL TECTONIC FRAMEWORK; IMBRICATION; LITHOSPHERE; MANTLE; MOSAIC; NORTHERN XINJIANG AND ADJACENT REGIONS; PLATE TECTONICS; Мезозой::Меловая; Мезозой::Юрская; Палеозой::Пермская; Палеозой::Каменноугольная; Докембрий::Протерозой::Неопротерозойская; Докембрий::Протерозой::Мезопротерозойская; Mesozoic::Cretaceous; Mesozoic::Jurassic; Paleozoic::Permian; Paleozoic::Carboniferous; Precambrian::Proterozoic::Neoproterozoic; Precambrian::Proterozoic::Mesoproterozoic